English for Maritime in Vocational High School Context; a Needs Analysis - Arfiyan Ridwan; Siti Maria Ulfa (Penerbit STKIP PGRI Bangkalan, 2018)
English for Specific Purposes (ESP) is an English learning that incorporates elements of the learner's specific needs and the context of the work environment. ESP for maritime or shipping is still not developed much in practice, especially in research. In Bangkalan city itself, there is a Shipping Vocational Middle School, but the development of supporting material for Maritime English is not optimal. This study aims to develop specific teaching materials to prepare maritime or sailing Vocational High School students to be able to equip themselves with work communication competencies in English. The R & D model used was the Language Development Program applied by Yalden (1987) comprising identifying the current situation and problems, referring it to the theory, obtaining needs analysis information, focus group discussion, writing manuscript, expert judgment, revision, tryout, and validation. It has been found that the language needs needed by seafarers are mostly in the context of coordination language onboard with the emphasis on speaking and reading, making notional-functional expressions are required to include in the materials. The results of the needs analysis are going to be used to next step, i.e. materials development.